EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS ASSISTED INDIVIDUALIZATION (TAI) DAN GROUP INVESTIGATION (GI) PADA POKOK BAHASAN KUBUS DAN BALOK DITINJAU DARI AKTIVITAS SISWA KELAS VIII SMP NEGERI SE-KABUPATEN KLATEN - W, Rahayu Sri; Kusmayadi, Tri Atmojo; Mardiyana, Mardiyana (Jurnal Pembelajaran Matematika, 2013)
ABSTRACT : The research aims to find out: (1) which students have the better learning achievement, the students who apply conventional learning model, TAI type of cooperative learning model, or GI type, (2) which students have the better learning achievement, the students who have high, medium, or low learning activities, (3) for each learning activities category, which of conventional learning model, TAI type of cooperative learning model, or GI type gives the better learning achievement, (4) for each type of learning model, which of the students with high, medium, or low learning activities gives the better learning achievement. This research was a quasi-experimental research with 3 Â´ 3 research design. The population was the grade VIII students of Public Junior High Schools in Klaten Regency in the second semester of grade year 2012/2013. Sampling technique was done by stratified cluster random sampling. Technique of analyzing data used was an unbalanced two way analysis of variance. Based on the results of the analysis, it can be concluded that: (1) the students who apply TAI type of cooperative learning model and GI type have mathematics learning achievement better than conventional learning model, while TAI type of cooperative learning model gives mathematics learning achievement as good as GI type, (2) the students with high activities has the best mathematics learning achievement compared to the students with medium or low activities, while the students with medium activities are better than the students with low activities, (3) for each activities categories of high, medium, and low, TAI type of cooperative learning model and GI type give mathematics learning achievement better than conventional learning model, while TAI type of cooperative learning model gives mathematics learning achievement as good as GI type, (4) for each learning models of conventional, TAI type, and GI type, the students with high activities has the best mathematics learning achievement compared to the students with medium or low activities, while the students with medium learning activities are better than the low one in the subject matter of the cube and block. Keywords: TAI, GI, Conventional, The Learning Activities.